ANALISIS SIKAP KONSUMEN TERHADAP ATRIBUT PRODUK KORAN SUARA MERDEKA - Setyowati, Ratih Widi; Suryoko, Sri; Nurseto, Sendhang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
PT. Suara Merdeka Press Semarang creates the products, Suara Merdeka newspaper with all the attributes that is stick; so that it can attach for providing a choice to society for determine the attitude in selecting paper products that is suitable with people desire and their needs. Â The purpose of this study is to determine how the attitude from consumer toward product attributes that is offered by the newspaper Suara Merdeka, in intrinsic attributes and extrinsic attributes.This study used descriptive research type survey method. The writer taken 100 respondents as a sample, the characteristics of respondents that are selected constitute the readers who do not subscribe read newspaper Suara Merdeka in Semarang area. The sampling method that is used is Accidental Sampling, and it use analysis method with method of attitudes Fishbein. Â The result shows that overall scores of consumer attitudes discovered like toward intrinsic attributes in Suara Merdeka newspaper. If it is viewed from the intrinsic attributes of global dimensions, then the consumer attitude towards the content and the types of news, feature attributes, includes like category, whereas aesthetic attributes includes ordinary category. From the consumer attitudes discovered that consumer like with extrinsic attributes Suara Merdeka newspaper. If it is viewed from the global dimension of extrinsic attributes, then the attitudes of consumers towards service reliability is an ordinary attribute, attribute of value self-expression, attributes of easiness and attributes of cost, three of them includes in like category. The conclusion from this research is that the general, the consumer attitudes towards attributes intrinsic and extrinsic attributes Suara Merdeka newspaper including like category. However, Suara Merdeka still need conducting an improvements to the global dimension that is the dimension of the details has consumer attitudes which includes in the ordinary category.